Administrative Digitalization and Performance Efficiency: The Moderating Role of Accountability in Public Sector Organizations in Nunukan Regency - Elda Apritia Puspita Dwi; Abdul Majid; Hasniaty (Universitas Muhammadiyah Makassar, 2026)
Public sector organizations increasingly adopt administrative digitalization to improve governance efficiency; however, empirical evidence regarding how digital transformation enhances performance efficiency and the role of accountability mechanisms remains limited, particularly in local government institutions. This study aimed to examine the effect of administrative digitalization on performance efficiency and to analyze the moderating role of accountability in public sector organizations in Nunukan Regency. The research employed a quantitative explanatory design using primary data collected through structured questionnaires distributed to employees of the Department of Social Affairs, Women’s Empowerment, and Child Protection in Nunukan Regency. A total sampling technique was applied, resulting in 50 respondents. Data were analyzed using SmartPLS with structural equation modeling to test direct and moderating relationships among variables. The results indicated that administrative digitalization had a positive and significant effect on performance efficiency, suggesting that the adoption of digital administrative systems improves operational processes and decision-making effectiveness. Accountability also showed a significant direct influence on performance efficiency. However, the interaction analysis revealed that accountability weakened the relationship between administrative digitalization and performance efficiency, indicating that additional accountability procedures may introduce administrative complexity that reduces the efficiency gains from digital transformation. These findings contribute to the literature on digital governance by highlighting the conditional role of accountability in shaping the effectiveness of digitalization initiatives. Practically, the study suggests that public sector organizations should balance digital transformation with streamlined accountability mechanisms to maximize efficiency improvements in administrative services.